ALTERNATIF SNACK UNTUK IBU HAMIL DAN MENYUSUI - Ani Nuraeni; Celine Marianti (Jurnal Gizi dan Kuliner, 2020)
The general purpose of this research is the development of snack products in the form of crackers. As for the purpose in particular (1) Reviewing crackers products made from katuk and green Beans, (2) reviewing the procurement of materials and equipment needs of products crackers Daun katuk and green Beans, (3) Reviewing the production activity crackers the leaves of the katuk and green Beans, (4) calculating the energy content and nutrient substances crackers the leaves of katuk and green beans, (5) analyzing the consumer's receiving power to the product crackers Catuk leaves and green beans , (6) Analyzing the cost of materials and selling price crackers the katuk leaves and green beans. The study began on 22 November 2018 until 29 November 2018 and continued on 21 March 2019 until 27 March 2019 at Dapur Kulinari and CA Gedung dieting, Sekolah Vocational School, Bogor. Data taken in the form of general condition data of culinary and diet laboratory, procurement of materials, production, marketing, energy content and nutrients crackers, consumer receipt, and cost of material crackers. Product development is an effort to find and develop products such as existing shapes and colors are then packaged more attractive to meet the customer satisfaction.The stages of product development starting from the procurement phase is the planning of the materials according to the type and amount required, purchase and storage of materials, production, and packaging. Purchases are made directly the day before production, while storage of materials consists of storage of dry materials and wet materials. Production activities include the preparation of tools and materials. Crackers Daun Katuk and green beans are processed with baking technique. Crackers are being pored into a package containing ten pieces. The content of energy and nutrients crackers one prescription amounting to 2774 Kal, 41.9 grams of protein, 167 grams of fat, 279.1 grams of carbohydrates, with a one-portion nutrient content of 277 Kal, 4.2 grams of protein, 16.7 grams of fat, and 27.9 grams of carbohydrates. The cost of the material used in the processing of dishes crackers katuk leaves and green beans in one production with a total cost of Rp 38,770 with the cost per serving of Rp 3,877. Selling price crackers Daun katuk and green beans per serving of Rp 10,000 with a percentage of profit of 38.77%. The Total cost of the product is two Rp 42,420 with the cost per serving of Rp 4,242. Percentage profit of 42.42% with a selling price of Rp 10,000. Keywords: Crackers, dwarf leaves, mung beans, pregnant and nursing mothers